Semantics Analysis of Sentence, Utterance, and Proposition in“Dear My Emotions” - Putri Cidi Adhisty; Hilma Safitri; Dimas Prasetyo; Devano Andhi Saputra (INDO PUBLISHING, 2025)
This research describes and identifies narratives within the framework of the semantic structures of the book